1984
DOI: 10.1083/jcb.99.2.569
|View full text |Cite
|
Sign up to set email alerts
|

Glycosyltransferase activities in Golgi complex and endoplasmic reticulum fractions isolated from African trypanosomes.

Abstract: Highly enriched Golgi complex and endoplasmic reticulum fractions were isolated from total microsomes obtained from Trypanosoma brucei, Trypanosoma congolense, and Trypanosoma vivax, and tested for glycosyltransferase activity . Purity of the fractions was assessed by electron microscopy as well as by biochemical analysis. The relative distribution of all the glycosyltransferases was remarkably similar for the three species of African trypanosomes studied . The Golgi complex fraction contained most of the gaIa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…In eukaryotes the ER is the site where secreted and membrane proteins are synthesized, modified and folded (rough ER) and where fatty acid and phospholipids are synthesized and metabolized (smooth ER). Both types of ER have been isolated from trypanosomatids [38]. For many of these processes an oxidized environment is required, and this is reflected in the relatively low glutathione\glutathione disulphide ratio found in the lumen of the ER (approx.…”
Section: Discussionmentioning
confidence: 99%
“…In eukaryotes the ER is the site where secreted and membrane proteins are synthesized, modified and folded (rough ER) and where fatty acid and phospholipids are synthesized and metabolized (smooth ER). Both types of ER have been isolated from trypanosomatids [38]. For many of these processes an oxidized environment is required, and this is reflected in the relatively low glutathione\glutathione disulphide ratio found in the lumen of the ER (approx.…”
Section: Discussionmentioning
confidence: 99%
“…As with other membrane-associated proteins, pre-VSG is synthesized with a rather long 30-40 amino acid hydrophobic NH2-terminal signal peptide, which is subsequently cleaved in the rough ER, where the molecule is synthesized (25). However, unlike eukaryotes, core glycosylation in trypanosomes appears to take place not in the rough ER but rather in some other organelle (tentatively assumed to be the smooth ER) (16). From pulse-chase experiments with L-[35S~methionine (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Its incorporation itito VSG is mediated by a dolichol monophosphate intermediate (9) and is inhibited by the antibiotic tunicamycin (11)(12)(13)(14). Recently, using highly enriched Golgi and endoplasmic reticulum (ER) fractions isolated from African trypanosomes (15,16), we tentatively concluded that inhibition of N-acetylglucosaminyl transferase by tunicamycin Al occurred only in the smooth ER subfraction, suggesting that core glycosylation of the VSG may occur in this organelle (16) and not in the rough ER, as previously assumed (10,11,13). As with any centrifugally prepared smooth ER subfraction, it is difficult to ascertain the ratio of ER to other vesiculated fragments of other membranous organelles.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The first one was carried out with African trypanosomes (Grab et al 1984). Transmission electron microscopy showed that the fraction consisted predominantly of smooth surface vesicles and flattened cisternae rather than stacked Golgi cisternae.…”
Section: Isolation Of the Golgi Complexmentioning
confidence: 99%